Intra-season changes in open-class amateur boxers` physiological profiles: A yearlong study - Davis, P. (Journal of Combat Sports and Martial Arts, 2017)
Introduction. Little is known of the physiological trainability of boxers and their reactions to current training strategy. Material and methods. Anthropometric, back/hand strength, upper-body plyometric power and 3x3 min running parameters were measured four times throughout the year and maximal oxygen uptake () at peak season. In twelve male open-class boxers (mean ± standard deviation) age: 22.7±2.7 yrs, height: 177.2±9.4 cm and body mass: 72.1±10.7 kg. Results. Surprisingly body mass, body fat, percentage body fat and total run distance showed no improvement throughout the season until peak season (all p<.002), 72.1 kg, 8.4 kg, 11.5 %, and 2548 m respectively. However this appeared to be at the expense of fat free mass which decreased by ~2 kg at peak season (p=.014). Furthermore, improvement beyond the starting levels at the start of the season for all parameters was never achieved. The results suggest that despite coach and boxer best efforts, training per-se does not necessarily result in the desired improvements. Conclusion. It is advised that boxers maintain a level of diet-control/training during holiday periods, this will allow the run-up to peak season to be about a controlled decrease of BF and maintenance or increase of fat free mass, strength and power. A simple set of tests should be used to track progress and identify areas that need improving. Strength, plyometric and individualisation of training should be implemented to improve the boxers` speed and power-endurance.